Hospital discharge planning: a qualitative study of new-graduate physiotherapists' experiences (Health Education in Practice: Journal of Research for Professional Learning, 2022)
Purpose: Discharge planning constitutes a large part of a physiotherapist's role when working in hospital settings. The challenges of decision-making relating to discharge planning have been identified by experienced physiotherapists. Despite known challenges associated with the transition from student to clinician, the experiences of new-graduates undertaking discharge planning are largely unknown. Therefore, this study aimed to explore:1)    new-graduate physiotherapists' experiences of discharge planning in hospital settings, and2)    the influence of pre-professional training on their perceived preparedness for discharge planning.Design: A qualitative general inductive approach using semi-structured interviews. New-graduate physiotherapists (n = 14) working in hospital settings were recruited.Finding: Four themes were generated: 1) responding to the pressures associated with discharging patients, 2) complex decision-making, 3) the role of the interprofessional team, and 4) desiring additional context and complexity from pre-professional training.Practice Implications: The study has identified that new-graduates underestimate the extent to which discharge planning features in their roles within hospital settings, and are unaware of the interprofessional practice required. Whilst they felt that their pre-professional training provides the technical skills required for their roles, they felt that they were not prepared for their role within the broader healthcare system, nor the complexity of clinical practice. This study encourages education providers to emphasise the role of physiotherapists within the broader health care system, through highlighting contexts where physiotherapy knowledge can be applied (i.e., discharge planning) and understanding the role of the physiotherapist within the interprofessional team.Limitations: Important perspectives of mentors and other members of the interprofessional team involved in discharge planning have not been included in this study which may have impacted the interpretation of the results.